A Label-free Sirtuin 1 Assay based on Droplet-Electrospray Ionization Mass Spectrometry - Sun, Shuwen (Anal Methods, 2016)
Sirtuin 1(SIRT1) is a NAD(+)-dependent deacetylase which has been implicated in age-related diseases such as cancer, Alzheimer’s disease, type 2 diabetes, and vascular diseases. SIRT1 modulators are of interest for their potential therapeutic use and potential as chemical probes to study the role of SIRT1. Fluorescence-based assays used to identify SIRT1 activators have been shown to have artifacts related to the fluorophore substrates used in the assays. Such problems highlight the potential utility of a label-free high throughput screening (HTS) strategy. In this work, we describe a label-free SIRT1 assay suitable for HTS based on segmented flow-electrospray ionization-mass spectrometry (ESI-MS). In the assay, 0.5 μM SIRT1 was incubated with 20 μM acetylated 21-amino acid peptide, which acts as substrate for the protein. A stable-isotope labeled product peptide was added to the assay mixture as an internal standard after reaction quenching. The resulting samples are formatted into 100 nL droplets segmented by perfluorodecalin and then infused at 0.8 samples/s into an ESI-MS. To enable direct ESI-MS analysis, 11 μM SIRT1 was dialyzed into a 200 μM ammonium formate (pH 8.0) buffer prior to use in the assay. This buffer was demonstrated to minimally affect enzyme kinetics and yet be compatible with ESI-MS. The assay conditions were optimized through enzyme kinetic study, and tested by screening an 80-compound library. The assay Z-factor was 0.7. Four inhibitors and no activators were detected from the library.